2012
DOI: 10.1093/alcalc/ags081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Ethanol Consumption in Experimental Sepsis

Abstract: These differences may be the result of either early mortality or an increase in the severity of the septic process. Taking into account the high mortality rate and the extreme severity of sepsis after alcohol consumption, often encouraged by advertising, a caution should be given to patients with severe infections and a history of alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…First, enrolment of subjects by administrative claims data may be less accurate, which is an inherent limitation to all database research. Evidence evaluating the impact of cigarette smoking [29] or alcohol consumption [34,35] on sepsis outcome is still limited and controversial. Nevertheless, it has been reported that obesity may increase the comorbidity of sepsis, but may not influence the mortality [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…First, enrolment of subjects by administrative claims data may be less accurate, which is an inherent limitation to all database research. Evidence evaluating the impact of cigarette smoking [29] or alcohol consumption [34,35] on sepsis outcome is still limited and controversial. Nevertheless, it has been reported that obesity may increase the comorbidity of sepsis, but may not influence the mortality [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…We have reported on the same sepsis induction model in male rats exposed to 10% ethanol/water as the only source of liquid for 4 weeks (13). Mortality was directly correlated to ethanol consumption, that is, rats that voluntarily consumed more ethanol (>11 g/kg) died earlier.…”
Section: Discussionmentioning
confidence: 98%
“…No significant differences were found in IL-4 and IL-13. Ethanol significantly decreased the effect of sepsis in the levels of IL-6 and TNF-α (13). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar rat model of polymicrobial sepsis using intraperitoneal injection of fecal material, Barros et al recently demonstrated a dose-dependent increase in mortality due to sepsis after chronic ethanol ingestion [21]. We hypothesize that this increased mortality is the result of the confluence of multiple immune deficits present in the conditions of both chronic alcohol ingestion and sepsis, but the identities of the key mediators of this effect are not yet known.…”
Section: Introductionmentioning
confidence: 87%